PENGARUH BUDAYA ORGANISASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN KARYAWAN PADA PT. BPR MAHA BHOGA MARGA - I Kadek Dony Septian Budi Utama; Ni Nyoman Suryani; I Nyoman Mustika (VALUES, 2021)
This study aims to determine the effect of organizational culture and work discipline partially and simultaneously on employee performance. The location of this research is PT. BPR Maha Bhoga Marga. The population uses employees of PT. BPR Maha Bhoga Marga and a sample of 38 employees. The data analysis technique used validity test, reliability test, classical assumption test, multiple linear regression analysis, coefficient of determination test, F test and t test. The results obtained from the research: (1) organizational culture has a significant positive effect on employee performance, where the t value is 2.030> t table 3.502 and a significance value of 0.001 <0.05. (2) work discipline has a significant positive effect on employee performance, where the t value is 2.030> t table 3.749 and a significance value of 0.001 <0.05. (3) simultaneously organizational culture and a significant effect on employee performance, where the t value is 22.925> F table 2.87 and a significance value of 0.000 <0.05. The amount of influence of the independent variables on employee performance is 54.2%. The suggestion that researchers can give is that PT. BPR Maha Bhoga Marga Kuta should guide employees, provide motivation to employees and periodically provide training to employees.